(untitled) (Fiep Bulletin - online, 2023)
The purpose of the research was to determine the relationship between the quality of service and the level of satisfaction of the students of the Faculty of Pedagogy and Physical Culture of the National University of Education, year 2019-2020. Quantitative, descriptive correlational study, applied to a sample of 259 students. Two questionnaires were used, with 5 dimensions and 17 items each. The results concluded that there is a moderate positive correlation between the variables: Quality of service and Level of satisfaction, (Spearman's Rho: 0.562). On the other hand, it was found that there is a moderate significant relationship between the tangible elements with the level of satisfaction (Spearman's Rho = 0.503), there is also a significant relationship between reliability and capacity with the level of satisfaction (Spearman's Rho = 0.566: Positive correlation moderate) and, finally, there is a relationship between security and empathy with the level of satisfaction (Spearman's Rho = 0.558: moderate positive correlation). The results agree with those of Huaita (2018), who established that the level of prediction of the variables work climate and job satisfaction together on teacher performance is at a statistically significant level; Regarding the tangible elements with the level of satisfaction of the study sample, similar results were found in the research by Hernández (2016); likewise, with studies by Álvarez, Botello, Chaparro, and Reyes (2015) who concluded that there is greater satisfaction between Ability to teach Teachers and the level of Self-realization of Students.